Pertanggungjawaban Pidana Terhadap Malpraktik Dalam Tindakan Medis Tanpa Izin (Studi Putusan Pengadilan Negeri Nomor: 109/PID.SUS/2019/PN KBU) - Mubarok, Sharul; Kadja, Thelma S. M.; Medan, Karolus Kopong (Artemis Law Journal, 2024)
Decision Number 109/pid.sus/2019/pn kbu pertains to the sentencing of a health worker for unlicensed practice and malpractice resulting in death. Despite the severity of the offense, the judge imposed only a Rp20,000,000 fine. This decision raises questions regarding its alignment with the defendant's actions and the considerations guiding the judge's sentencing. The research, utilizing a normative juridical approach, analyzed primary, secondary, and tertiary legal materials. This method aims to uncover truth through legal logic from a normative perspective. Findings indicate that the judge's decision inadequately reflects the gravity of the defendant's actions. Apart from operating without a license, the defendant's negligence led to substandard medical practices resulting in death. However, the judge dismissed the element of negligence causing death, citing the need for proof of the causal relationship between the defendant's actions and the victim's demise. The prosecution should have presented forensic autopsy evidence to establish this link. Furthermore, the judge should have considered non-juridical factors such as justice, legal certainty, and public safety in sentencing the defendant.